Systematic Review: Effectiveness of Health Promotion in Preventing Non-Communicable Diseases in the Digital Era - Fikriyah Arfina Nainggolan; Agustatius Sitepu; Anna Tirawani Ambarita (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Noncommunicable diseases (NCDs) are the leading cause of death globally and continue to rise, including in Indonesia. Unhealthy lifestyle changes among the population are a major factor in the rise of NCDs, necessitating effective promotive and preventive strategies. With the advancement of digital technology, health promotion has undergone a transformation through the use of digital media such as mobile health (mHealth), social media, and short message service (SMS). However, the effectiveness of digital health promotion in preventing NCDs still yields mixed results. This study aims to enhance the effectiveness of digital health promotion in preventing NCDs through a Systematic Literature Review (SLR) approach. The research method follows the PRISMA guidelines, with a literature search based on data from Scopus, PubMed, and ScienceDirect for articles published between 2020 and 2025. Inclusion criteria included Scopus-indexed journals discussing digital interventions in health promotion, while articles in the form of opinions, editorials, and studies without empirical data were excluded. A total of 15 articles met the criteria and were analyzed narratively. The results indicate that digital health promotion is consistently effective in increasing public knowledge and awareness regarding NCD prevention. However, its impact on changes in health behavior remains variable. Mobile health (mHealth)-based interventions demonstrated higher effectiveness in increasing physical activity and reducing body mass index (BMI), while SMS-based interventions were shown to improve adherence to healthy eating patterns. In general, digital health promotion has moderate effectiveness in influencing public health behavior. The study’s conclusions indicate that digital health promotion is a promising strategy for NCD prevention, but requires further development—particularly in integrating behavioral change theory, enhancing user engagement, and ensuring equitable access to technology. Future research is recommended to develop more interactive, personalized, and sustainable interventions to enhance the effectiveness of long-term behavioral.